Urban Housing and Social Capital as Key Factors in Implementation of Recycling Policy. The Case Study of the New Recycling Program in Rome - Martire, Fabrizio; Barbanera, Lorenzo; Floridi, Federica; Fusillo, Federica; Palmieri, Marco (Italian Sociological Review, 2022)
When the recycling policy expects to change the citizens’ behaviour, its implementation needs to be planned carefully, inquiring in advance the contextual factors that may interact with the actions planned by the policymakers. The connection between the actions planned on the desk and the characteristics of local context, where the policy impacts, is even more important when the relationship between the institutional policymakers and the citizens is conflictual. In this case, a vertical top-down approach in the policy implementation is not suggested, and a participatory bottom-up strategy should be employed, promoting popular consensus and trust in the environmental policy. The paper reports the case study of the new recycling program in Rome. The study shows that the delays and the problems encountered by the policymakers are due to the rigid top-down implementation and the low involvement of citizens and grassroot associations in designing the new recycling program, planned to change the everyday lives of people. The results identify the key contextual factors of recycling policy’s success: the urban housing and the social capital of people.